Content and competencies to be highlighted and incorporated into technical training for the care of the elderly in Colombia, Costa Rica and Uruguay - Leiva Marín, Monica (2024)
Human resources to provide formal long-term care for the elderly are growing demand in Latin America. There is a lack of training in the caregiving workforce in the region, prompting governments to prioritize training as the develop their Care Systems. The aim of this study is to analyze the contents included in technical training programs offered in Colombia, Costa Rica and Uruguay, and compare them with the educational needs and interest reported by caregivers, as well as with international study programs and training that incorporate the person centered care approach. This descriptive study used a mixes methods approach, applying a concurrent triangulation strategy of qualitative and quantitative data. A documentary review of eight caregiving curricula from the three countries was conducted to identify content, and 109 caregivers were surveyed between November 2021 and March 2022, inquiring about work conditions, challenges, and educational interests. The identified contents were organized around five dimensions that cut across the person centered care approach. There was a greater emphasis on topics related to acquiring skills for healthcare and establishing daily care routines, compared to topics related to humane treatment and the development of personalized plans with the elderly, which were among the most mentioned by caregivers. Further research needed to understand the educational interests of caregivers. And to delve into programs in more countries in the region.